บทบาทของภาคีหุ้นส่วนในการส่งเสริมปรัชญาเศรษฐกิจพอเพียงในสถานศึกษาสังกัดสำนักงานคณะกรรมการการอาชีวศึกษา : พหุกรณีศึกษา - สุชีรา วิบูลย์สุข (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purposes of this research were 1) to study the roles and strategies of the boundary partners in supporting the sufficiency economy philosophy based on 5 thinking frame value "enough to sufficient" 2) to study the results obtaining from the operated roles, and 3) to evaluate the success of the sufficiency economy philosophy support applying the outcome mapping, This research was operated by a multiple case study method at 2 colleges. The research data were collected by reviewing related documents, participatory and non- participatory observations as well as interview and group meeting based on the concept of outcome mapping. Content analysis, comparison and inductive conclusion were employed to analyze the research data. The research findings were as follows: 1. As for the roles and strategies found that the first important boundary partners was the leading of administrators and The supporting strategies used was a seminar for staff and fulfill the concept with agricultural project and money saving project. The second boundary partners was teachers who were influence in teaching the theory of sufficiency economy and applied to use and raise the students awareness, used the techniques of integrating and implementing the idea for the uses in daily life. And the students were supported from the teachers with the various types of teaching methods and applied the knowledge to use in daily life. The strategies which were used are co-operation in projects and activities that the colleges provided.2. The results gains from the operations of boundary partners found that the administration of the directors discovered that both colleges applied to use the sufficiency economy philosophy to manage that effect the sufficient career college to increase the staff income and develop the learning resources, the sufficient technical college emphasized on scattering work load systematically, reduced the conflict of organization, focus on money saving, daily accounting emphasized on generating ethical career in students. Both colleges improved the environment that facilitate learning, gave community services with willingness. In the teachers’ approach found that both colleges used implementing idea of sufficiency economy philosophy, ethic, also developed the invention with the sufficiency economy philosophy idea. And the quality of students’ lives found students applied to use the sufficiency economy philosophy, saving and making the most use and reason in spending, obtaining skills extra curriculums are the new agriculture theory and money saving, and the students applied in using money. 3. The result of achievement of supporting the sufficiency economy philosophy by applying the outcome mapping found that in level expect to see of teachers in both colleges, there were operated according to the criteria of progress in all items. In the part of sufficient technical college, there were the operations in all items of the criteria. The operation of sufficient technical college has not finished in all items. In level like to see of teachers and students has not finished the operations in all criteria items, and level love to see there were no operations for teachers and students in both colleges.